Dengue control in Ribeirão Preto, São Paulo, Brazil - Passos Afonso Dinis Costa; Rodrigues Eugênia Maria Silveira; Dal-Fabbro Amaury Lelis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Following an epidemic of type I dengue in late 1990, the municipality of Ribeirão Preto (State of São Paulo, Brazil) assumed direct responsibility for the control of Aedes aegypti larvae. Control activities are presented in this report and are based on popular participation and environmental management. Massive use of the communications media, participation by schoolchildren, constant contact with the population, and integration of various public agencies are the program's priorities. Although the drop in the number of susceptibles may have played a role in the reduction of cases after the initial epidemic, the intense preventive campaign certainly helped quell the disease in the city, since changes were observed in the behavior of the population towards potential breeding sites. The occurrence of new cases in recent years appears to be related to greater circulation of the virus in both the State of São Paulo and Brazil as a whole, indicating the need for control measures at the national and continental level, without which it will be difficult to maintain low transmission rates, even in areas submitted to intense preventive work.